2014
DOI: 10.1161/strokeaha.113.001721
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Predicts Hematoma Growth in Intracerebral Hemorrhage

Abstract: Inflammation is a major feature of sICH pathology, [3][4][5] and inflammatory markers on admission, such as fever, elevated white blood cell (WBC) count, interleukin-6 (IL-6), and fibrinogen are associated with worse short-term outcomes. 3,5,6 C-reactive protein (CRP), an acute-phase reactant induced by IL-6, is associated with 30-day mortality in ICH patients, 7 but its relationship with EHG is unknown. Our primary goal was to determine the link between CRP and EHG after sICH. As a secondary objective, we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 31 publications
1
69
1
Order By: Relevance
“…We screened 4191 studies identified by our searches, assessed 167 for eligibility, invited 77 eligible cohorts to share data, and obtained patient-level data from 36 (47%) cohorts18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 involving 6428 patients with repeat brain imaging after intracerebral haemorrhage between 1985 and 2015 (no data up to 1984 were obtained; figure 1; appendix). 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 Countries classified as high income by the World Bank contributed to 26 (72%) of 36 collaborating cohorts versus 30 (73%) of 41 eligible cohorts that did not collaborate.…”
Section: Resultsmentioning
confidence: 99%
“…We screened 4191 studies identified by our searches, assessed 167 for eligibility, invited 77 eligible cohorts to share data, and obtained patient-level data from 36 (47%) cohorts18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 involving 6428 patients with repeat brain imaging after intracerebral haemorrhage between 1985 and 2015 (no data up to 1984 were obtained; figure 1; appendix). 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 Countries classified as high income by the World Bank contributed to 26 (72%) of 36 collaborating cohorts versus 30 (73%) of 41 eligible cohorts that did not collaborate.…”
Section: Resultsmentioning
confidence: 99%
“…57 In addition, peptic ulcers have been reported to upregulate IL-6, 58 with a subsequent rise is CRP levels, which in turn may predict gastrointestinal bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…56 CRP levels were even found to predict early hematoma outgrowth after ICH. 57 In addition, peptic ulcers have been reported to upregulate IL-6, 58 with a subsequent rise is CRP levels, which in turn may predict gastrointestinal bleeding events. [59][60][61] Additionally, we previously found that anti-HPA-1a antibodies can reduce endothelial cell spreading and monolayer integrity, possibly affecting bleeding tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Patient registration years ranged from 1993 to 2014, with 90% of patients from 2004 to 2013. Registry methods are summarized in Supplementary Table I, with further details previously published 2, 3, 4, 14, 15, 16, 17, 18, 19, 20…”
Section: Methodsmentioning
confidence: 99%